Phase Transitions in Highly Anisotropic Ternary TlGaSe2 Crystals Studied by High-Resolution Optical Spectroscopy - Pashayev, A.M.; Asgarov, K.A.; Allahverdiyev, K.R. (Herald of Azerbaijan Engineering Academy, 2025)
The infrared and terahertz spectroscopy of TlGaSe2 crystals has been studied over a wide temperature range (3  325 K). The appearance of new phonon modes in the TlGaSe2 spectra below a temperature of T = 120K was detected, due to a structural phase transition; the phonon parameters of the crystal under study revealed features at temperatures of 30K, 60K, and 92.5K. The observed anomalies have been explained as related to the reaction of phonons to the formation of an antisegnetoelectric structure and a change in the latter with temperature. Splitting of some phonon modes at 60K may occur due to symmetry breaking due to increased interaction between two polar sublattices.